2023
DOI: 10.1039/d2cp05155a
|View full text |Cite
|
Sign up to set email alerts
|

Pyrene aggregation at unprecedented low concentrations in (lanthanide metal salt + urea) deep eutectic solvents

Abstract: We report intermolecular excimer formation by a common and popular polycyclic aromatic hydrocarbon pyrene at very low concentrations (low µM) when dissolved in deep eutectic solvents constituted of hydrated lanthanide...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Herein, we report our findings of exceptionally high probe-reported polarity exhibited by a set of type IV DESs constituted of hydrated lanthanide metal salts as HBA and urea as prototypical HBD [14]. These DESs have recently shown to support probe aggregation at unprecedented low concentrations [20]. Specifically, three (3) HBD urea-based DESs containing HBA metal salts lanthanum nitrate hexahydrate (La : U), cerium nitrate hexahydrate (Ce : U), and gadolinium nitrate hexahydrate (Gd : U), respectively, are found to exhibit some of the highest probereported polarities in terms of empirical Kamlet-Taft parameters of dipolarity/polarizability (π*) [21] and HBD acidity (α) [22] along with ET values [22].…”
Section: Introductionmentioning
confidence: 91%
“…Herein, we report our findings of exceptionally high probe-reported polarity exhibited by a set of type IV DESs constituted of hydrated lanthanide metal salts as HBA and urea as prototypical HBD [14]. These DESs have recently shown to support probe aggregation at unprecedented low concentrations [20]. Specifically, three (3) HBD urea-based DESs containing HBA metal salts lanthanum nitrate hexahydrate (La : U), cerium nitrate hexahydrate (Ce : U), and gadolinium nitrate hexahydrate (Gd : U), respectively, are found to exhibit some of the highest probereported polarities in terms of empirical Kamlet-Taft parameters of dipolarity/polarizability (π*) [21] and HBD acidity (α) [22] along with ET values [22].…”
Section: Introductionmentioning
confidence: 91%
“…More recently, Pandey et al observed that pyrene exhibits an intermolecular excimer at low concentrations (20 mM) in deep eutectic solvents constituted of hydrated lanthanide salts and urea. 75 Thus, spectroscopic analysis is the preferred analytical technique to identify the aggregation behaviour of pyrene-based luminogens.…”
Section: The Aggregation Behaviour Of Pyrene-based Emitters In Solutionmentioning
confidence: 99%